Mobilization of peripheral blood progenitor cells for human immunodeficiency virus-infected individuals - Law, Ping; Lane, Thomas A; Gervaix, Alain; Looney, David; Schwarz, Lamia; Young, Dennis; Ramos, Silvestre; Wong-Staal, Flossie; Recktenwald, Diether; Ho, Anthony Dick (Experimental hematology, 1999)
Gene therapy is becoming one of the most promising modalities for the treatment of acquired immunodeficiency syndrome. The purpose of this study was to investigate the mobilization and collection of peripheral blood progenitor cells from human immunodeficiency virus (HIV)-infected individuals using granulocyte colony-stimulating factor (G-CSF). A total of 10 patients (9 male, 1 female; median age 36.5 years) with varying circulating CD4+ cell counts (13.9-1467/μL) were administered 10 μg/kg G-CSF daily for 6 days. Peripheral white blood cells (WBCs), CD34+ cell counts, lymphocyte subsets, and plasma viremia were monitored before each G-CSF injection. An average sixfold increase in WBCs was observed, which stabilized on day 4 or thereafter. The level of CD34+ cells was increased by 20-fold, and did not differ between days 5 and 6. Smaller increases in CD4+, CD8+, and CD4+CD8+ cells were observed. HIV viral load, as measured by RNA copy number in plasma, was not significantly altered by G-CSF administration. The leukapheresis product (LP), collected on day 7, contained an average of 6.25 ± 4.52 (mean ± standard deviation) × 1010 WBCs and 3.08 ± 2.98 × 106 CD34+ cells/kg. The levels of different CD34+ cell subsets were similar to those in the LPs of G-CSF-mobilized healthy individuals from an earlier study. Primitive hematopoietic cells (CD38− and CD38−HLA-DR+ cells) were detected in LPs (1.19 ± 0.46% and 0.87 ± 0.23%, respectively, of CD34+ cells). All parameters (WBC counts, lymphocyte populations, CD34+ cells, and HIV-1 RNA copies) measured 3 weeks after leukapheresis returned to baseline values. The administration of G-CSF was well tolerated by the HIV patients; side effects included bone pain, headache, flu-like symptoms, and fatigue. There were no correlations between baseline CD4+ cell count and the WBCs, mononuclear cells, or CD34+ cells collected in the LP. Similarly, no correlation existed between baseline CD4+ and CD34+ cells, peak CD34+ cells, or days to achieve peak CD34+ cell counts after G-CSF mobilization. Our results showed that: (1) maximal mobilization can be achieved after 4 days of G-CSF administration; (2) therapeutic quantities of hematopoietic cells can be collected and used for gene therapy; and (3) G-CSF administration is well tolerated and does not cause a clinically significant increase in viremia.